GEMOHING IN LAMAHOLOT OF EAST FLORES: THE FOUNDATION AND PILLAR OF RELIGIOUS MODERATION - Atasoge, Anselmus Dorewoho; Sihombing, Adison Adrianus (Balai Penelitian dan Pengembangan Agama Semarang, 2022)
Gemohing is a local culture of the Lamaholot people. Gemohing has had a significant impact on the attainment of the ideals of mainstreaming religious moderation in Indonesia. This study aimed at exploring the expression of gemohing as the foundation and pillar of religious moderation for the people of East Flores. This study is qualitative, built upon primary and secondary data. The primary data were collected from observations on community participation. While the materials were directly gathered from the gemohing practice and interviews with 23 cultural figures and residents of the gemohing tradition. Secondary data were obtained from relevant preceding studies and two documentary films about the practice of gemohing. Both types of data were analyzed qualitatively-interpretatively. This study was conducted from September 2019 to July 2022 in the Larantuka, Adonara, and Solor. This study found that the Lamaholot community demonstrated gemohing as the foundation and pillar of building a shared life. The gemohing praxis which is based on the Lamaholot philosophy is reflected in the principles of ina tou ama ehang and puin taan tou gahan taan ehan. These principles mean that all Lamaholot people come from one mother and father and therefore the spirit of unity must be upheld. They mandate that every citizen views each other as brothers that need to be appreciated and respected with a spirit of unity in the social order and as an individual as well. From this point of view, unity and oneness are highly emphasized aspects. This study represents a contribution to efforts to promote religious moderation.